Foucault panoptizmas ir (savi)priežiūra: nuo individų prie dividų. - Kaziliunaite, Aušra (Problems / Problemos, 2020)
The paper analyses the concept of panopticism formulated in Foucault's works and its possibilities of relevance in contemporary power and (self)surveillance studies. In the book "Discipline and Punish: The Birth of the Prison", Foucault, applying Jeremy Bentham's idea of a panoptical prison, writes about the power of the sovereignty that is replaced by the society of discipline. Foucault discusses panopticism in order to unfold the concept of the society of discipline. Here the essential measure of the society of discipline and panopticism becomes the concern for the individual per se. Deleuze in his text "Postscript on the Societies of Control" states that we no longer live in a society of discipline, but rather in a process, where we switch from the society of discipline to the society of control. In these changed circumstances, according to Deleuze, there are no longer individuals, rather dividuals. In these circumstances, is it possible to talk about panopticism? The paper shows that panopticism is still relevant while switching to the society of control. Also, it states that the currently unfolding scheme of the society of control has been programmed in the asymmetry of the panoptical gaze. Precisely in the processes produced in the asymmetry of the gaze gain its flexible totality in the society of control.